Peranan Bioteknologi Dan Mikroba Endofit Dalam Pengembangan Obat Herbal - Radji, Maksum (UI Scholars Hub, 2005)
Plants have been the chief source of compounds of medicine for thousand of years. Plants are also the source of many medicines for the majority of the worldÂ’s population. The role of biotechnology is very important for multiplying, conserving the spesies, and enhancing the production of secondary metabolites. Endophytes are microbes that inhabit plants are currently considered to be a wellspring of novel secondary metabolites offering the potensial for medical and industrial exploitation. Natural products from various endophytic microbes have been investigated. Some examples of natural products observed from endophytic microbes are antibiotics, antiviral compounds, anticancers, antimalarial compounds, antioxidants, antidiabetics, and immunosuppressive compounds.